Lansium domesticum: A natural dual-action defence against dengue mosquitoes - Reni Yunus; Anita Rosanty (Jurnal Teknologi Laboratorium)
Preventing dengue virus transmission, which leads to Dengue Hemorrhagic Fever (DHF), can be effectively achieved using plant-based insecticides. This study investigates the potential of Lansium domesticum extract as both a repellent and a larvicide against Aedes aegypti, the primary vector of dengue fever. Five concentrations of Lansium domesticum extract (10%, 20%, 30%, 40%, and 50%) were tested for their repellent properties, while larvicidal efficacy was evaluated at concentrations of 20%, 40%, 60%, 80%, and 100%. The evaluation of larval mortality obtained an average larval mortality of 5%-20%, then a statistical analysis was carried out using the Anova test. Furthermore, probit analysis was carried out to determine the LC50. Results showed that all concentrations had a repellency rate greater than 50%. The larvicidal tests indicated that the 100% concentration was the most effective in killing larvae. These findings highlight Lansium domesticum as an effective natural repellent and larvicide against Aedes aegypti, offering a promising plant-based solution for dengue fever prevention.